1994
DOI: 10.1128/iai.62.2.589-595.1994
|View full text |Cite
|
Sign up to set email alerts
|

Differences in complement activation between complement-resistant and complement-sensitive Moraxella (Branhamella) catarrhalis strains occur at the level of membrane attack complex formation

Abstract: The mechanism of resistance to human complement-mediated killing in Moraxella catarrhalis was studied by comparing different complement-sensitive and complement-resistant M. catarrhalis strains in a functional bystander hemolysis assay and an enzyme-linked immunosorbent assay (ELISA) for soluble terminal complement complexes. Complement-resistant stains appeared to activate complement to the same extent as, or even slightly better than, complement-sensitive strains. This indicates that complement-resistant str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…In contrast, M. catarrhalis strains isolated from the upper respiratory tract of healthy children are primarily (58%) sensitive to complement-mediated killing. It was established that resistant strains inhibit complement activity at the level of the formation of membrane-attack complexes [11]. In addition, it was demonstrated that complement resistance is possibly facilitated by one of the outer membrane proteins, designated high molecular mass outer membrane protein (HMW-OMP) or ubiquitous surface protein (UspA) [5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, M. catarrhalis strains isolated from the upper respiratory tract of healthy children are primarily (58%) sensitive to complement-mediated killing. It was established that resistant strains inhibit complement activity at the level of the formation of membrane-attack complexes [11]. In addition, it was demonstrated that complement resistance is possibly facilitated by one of the outer membrane proteins, designated high molecular mass outer membrane protein (HMW-OMP) or ubiquitous surface protein (UspA) [5,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the multitude of other antigenic proteins was still sufficient to facilitate IgG-binding, or that small changes in IgG-binding, not detected by flow-cytometry, caused attenuated complement resistance. Along the same line, Verduin et al showed that complement resistant isolates activated complement to the same extent or slightly better than complement sensitive isolates, and that the activation of complement was IgG-dependent (Verduin et al, 1994).…”
Section: Discussionmentioning
confidence: 92%
“…Our results, however, suggest that UspA2 binds vitronectin. While binding of pathogens to vitronectin has been linked to cell adherence and invasion (6,7,16), van Dijk and his coworkers reported that vitronectin binding by M. catarrhalis may subvert host defenses (27). The soluble form of vitronectin is also known as S-protein in the complement system, and it regulates the formation of the membrane attack complex (25).…”
Section: Discussionmentioning
confidence: 99%